Remission of symptoms among schizophrenia patients receiving assertive community treatment (ACT) in Malaysia: one year follow-up - Rahima Dahlan,; Marhani Midin,; Hatta Sidi, (Universiti Kebangsaan Malaysia, 2013)
Assertive community treatment (ACT) is one of the most important elements of mental health care reform in Malaysia. Many studies worldwide have reliably found that ACT has positive impact on several outcome domains such as reduced hospitalization rate, improvement of symptoms and quality of life. This study aimed to assess the outcome of ACT in the aspect of symptom remission and its influencing factors among patients with schizophrenia in the urban city of Kuala Lumpur. A cross sectional study was conducted on 155 patients with schizophrenia who received ACT in Hospital Kuala Lumpur (HKL). The selection was made by simple random sampling. The abbreviated Brief Psychiatric Rating Scale (BPRS) was used to determine the status of symptom remission. The socio demographic and relevant clinical data were also assessed. A total of 76% (118) was noted to be in remission. According to logistic regression, the strongest predictor of patients receiving ACT with symptom remission was having good social support (p<0.001) and with higher educational level (p=0.024). The study revealed the effectiveness of ACT in terms of high prevalence of patients with symptom remission. This was despite the model of ACT being studied not fulfilling all fidelity measurements of the standard version of the service. The finding would hopefully act as a propeller for further development in this service area. However, the study needs to be replicated through studies with better designs and involving more psychiatric centers.